The Case Study Of Taman Buaya Langkawi Sdn. Bhd. - Kam, Tay Eue (2004)
In this case study , analysis tools such as the SWOT analysis, Ansoff Model, Space Analysis and Boston Consulting Group Model were used. The recommendation for Taman Buaya Langkawi is to move forward more aggressively to tap into the international market.